2018
DOI: 10.1186/s40623-018-0965-7
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids on witness coupons collected from the ISAS/JAXA curation facility for the assessment and quality control of the Hayabusa2 sampling procedure

Abstract: The Hayabusa2 mission aims to obtain pristine samples from a near-Earth carbonaceous-type (C-type) asteroid, 162173 Ryugu, and return them to Earth. One of the scientific goals of the mission is to understand the origin and evolution of organic materials through the interactions between water and minerals in the early solar system. Thus, organic materials are the main focus of the analysis on the returned samples. The analysis of extraterrestrial organic materials, however, requires great care to avoid the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The total abundance of amino acids detected on the witness coupon that had been exposed to the clean chamber environment for 7 days was 0.3-1.2 ng/cm 2 . The most abundant terrestrial contaminant was glycine, which was accumulated at a calculated rate of 1.2 pmol (∼0.09 ng) /cm 2 /day (Sugahara et al 2018). This level of terrestrial deposition of glycine is low, compared to the amount of glycine detected in extra-terrestrial samples returned by space missions (e.g.…”
Section: Contamination Control Measuresmentioning
confidence: 95%
See 2 more Smart Citations
“…The total abundance of amino acids detected on the witness coupon that had been exposed to the clean chamber environment for 7 days was 0.3-1.2 ng/cm 2 . The most abundant terrestrial contaminant was glycine, which was accumulated at a calculated rate of 1.2 pmol (∼0.09 ng) /cm 2 /day (Sugahara et al 2018). This level of terrestrial deposition of glycine is low, compared to the amount of glycine detected in extra-terrestrial samples returned by space missions (e.g.…”
Section: Contamination Control Measuresmentioning
confidence: 95%
“…Witness coupons made from aluminium foil that were exposed in a clean chamber in the curation room at the ESCuC sample curation facility of JAXA were analysed in order to examine the type of contaminants and their accumulation rates (Sugahara et al 2018). Common terrestrial amino acids (glycine, alanine, valine, leucine, isoleucine, proline, aspartic acid and glutamic acid) were detected.…”
Section: Hayabusa Mission (2003-2010)mentioning
confidence: 99%
See 1 more Smart Citation
“…Quality control for the sample process, including in ground-based procedures, is an important issue for sample return missions. The ESCuC (the Extraterrestrial Sample Curation Center) in the ISAS/JAXA facility (Yada et al, 2014;Uesugi et al, 2019) was assessed by an interlaboratory evaluation, and Sugahara et al (2018) reported an assessment of the clean room at ISAS/JAXA, which is intended to be used in the processing Hayabusa2 samples (cf. assessment on the OSIRIS-REx mission; Dworkin et al, 2017).…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…From an observational perspective, a large segment of astrobiological exploration today is focused on locating and quantifying amino acids in stellar environments. This includes astronomical observations and theory [30,[39][40][41] as well as space missions to search for amino acids in comets and asteroids [42,43].…”
Section: Introductionmentioning
confidence: 99%